PELAKSANAAN KETENTUAN TENGGANG WAKTU PENDAFTARAN PERALIHAN HAK MILIK ATAS TANAH KARENA SEBAB PEWARISAN DI TINJAU MENURUT PASAL 61 AYAT (3) PP NOMOR 24 TAHUN 1997 DI SAMARINDA - Aldi Arfahksyadz (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACS  Pursuant to Article 61 paragraph 3 of Government Regulation No. 24 of 1997 states that: If a person has the right to land has died, the rights as heirs must register their rights in a grace period of 6 (six) months after the death of the person, not charged registration. Of the provisions of article above that the existence of legal events in the form of inheritance, it can be said that the heirs accept the transition of property rights as the heir must register their right transition to the Office of National Defense. In a grace period of 6 (six) months after the death of the testator must be registered, it is intended in order to issuance of new certificates on behalf of the heirs concerned and that certainty and legal protection for rights holders new property. The registration of transfer of rights for inheritance is done directly by the rights holder / or the heir to the Office of the National Land with accompanying documents must be satisfied that the respondent register transition of property rights for inheritance carried through the ravine as many as 18 respondents or 60% who make application through the intermediary of notary services as much as 9 respondents or 27%, and the register transfer of rights for the individual inheritance by 7 respondents or 19%.